Assessment of Techniques Employed by Basic Teachers in Reducing Pupils Undesirable Behaviours in Classrooms in Ilorin South Local Government Area of Kwara State - Banun Havifah Cahyo Khosiyono; Rafiu Abdulwahab; Folarin Moruf Oluwafemi; Jamiu Temitipe Sulaimon (TAMANSISWA INTERNATIONAL JOURNAL IN EDUCATION AND SCIENCE, 2023)
The purpose of this research is to examine the Techniques Employed by Basic Teachers in Reducing Pupils Undesirable Behaviours in Classrooms in the Ilorin South Local Government Area of Kwara State, Nigeria. Recently, the issue of undesirable behaviors among children in our society today and the world at large specifically in schools has become worrisome and a major cause for concern for parents, teachers, educational stakeholders, and other related agencies in the field. This study adopted a descriptive type of research design. The study comprised all public primary school teachers in Ilorin South. Multi-phasic sampling techniques were used in this study that is, Purposive and proportional sampling techniques were used to select one hundred and eleven (111) qualified basic school teachers across the fifteen (15) selected schools while the fifteen (15) schools selected using simple random sampling techniques. The research instrument employed was a researcher’s designed questionnaire in which the test re-test reliability method was used to determine the validity and reliability of the instrument using Pearson product-moment correlation (PPMC) and a co-efficient of 0.93 was established. The findings from this study showed that Teachers’ years of experience, age and educational qualification have a significant influence on the kind of techniques employed by the teachers while teachers’ gender was found not to have any significant influence on the kind of techniques they employed. The recommendation was made based on these findings.